2022
DOI: 10.1111/1471-0528.17138
|View full text |Cite
|
Sign up to set email alerts
|

Is care of stillborn babies and their parents respectful? Results from an international online survey

Abstract: Objective: To quantify parents' experiences of respectful care around stillbirth globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Despite recent medical advances, disrespectful care was still described by parents in perinatal bereavement practice. 10 This suggests that nurses and midwives need to receive relevant trainings so that they can be fully prepared to provide high-quality perinatal bereavement care for parents. Therefore, it is important to explore a dependable and effective PBCTP that can be disseminated quickly and promptly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent medical advances, disrespectful care was still described by parents in perinatal bereavement practice. 10 This suggests that nurses and midwives need to receive relevant trainings so that they can be fully prepared to provide high-quality perinatal bereavement care for parents. Therefore, it is important to explore a dependable and effective PBCTP that can be disseminated quickly and promptly.…”
Section: Discussionmentioning
confidence: 99%
“…7 9 Disrespectful care of parents and infants was reported. 10 Nursing professionals experience challenges such as a lack of perinatal bereavement care confidence (PBCC), heavy emotional burden and insufficient organisational support. 11 Recently, published results revealed that systematic training was an essential influencing factor of midwives' perinatal bereavement care competence.…”
Section: Introductionmentioning
confidence: 99%
“…No themes were related to spending time with their baby or making memories, however, subsequent research has challenged the concept that this opportunity is unwanted by parents in low and middle income countries. 86 …”
Section: Care After Stillbirthmentioning
confidence: 99%
“…An analysis of 3769 parents’ experiences of stillbirth gathered through a 2015 survey found that parents in middle income countries were less likely to report respectful care after their baby was stillborn compared with parents in high income countries (351/619 (57%) v 2462/3150 (78%); odds ratio 0.37 (95% confidence interval 0.30 to 0.44)). 86 Parents in middle income countries also felt less involved in decision making, a principle common to all three existing national bereavement care guidelines. As such, urgent attention is needed to develop, implement, and evaluate bereavement care guidelines.…”
Section: Care After Stillbirthmentioning
confidence: 99%
“…Women who experience perinatal loss often receive unsatisfactory care, feeling that the care they received did not meet their expectations ( 4 ). An online survey done in 44 high-and middle-income countries reported that 25.4% of 3,769 bereaved parents reported disrespectful care and 23.5% reported disrespectful care of their baby ( 5 ).…”
Section: Introductionmentioning
confidence: 99%